The Müllerian HOXA10 gene promotes growth of ovarian surface epithelial cells by stimulating epithelial-stromal interactions - Ko, Song Yi (2009)
The ovarian surface epithelium (OSE) origin of ovarian cancers has been controversial because these cancers often exhibit Müllerian-like features. One hypothesis is that ovarian neoplasia involves the gain of growth advantages by OSE cells via activation of Müllerian programs. The homeobox gene HOXA10 controls formation of the uterus from the Müllerian ducts, and is not expressed in normal OSE. We previously found that HOXA10 is expressed in ovarian cancers with endometrial-like features, and induces transformed OSE cells to form glandular tumors in mice. In the current study, we found that induction of HOXA10 in OSE cells promotes homophilic cell adhesion and prevents anoikis. HOXA10 expression stimulated interactions of OSE cells with the extracellular matrix proteins vitronectin and fibronectin, and with mesothelial cells of the omentum which is a common attachment site for ovarian cancer cells. HOXA10 also stimulated interactions of OSE cells with omental fibroblasts, and these interactions promoted OSE cell growth. Our findings indicate that aberrant activation of a Müllerian program in OSE cells confers growth advantages by stimulating cellular interactions with the microenvironment.